Association between 24 h Urinary Sodium and Potassium Excretion and Dietary Intake in Japanese Male Adolescent Football Players - Yosuke Nagashima; Akiko Horikawa; Mari Mori (MDPI AG, 2021)
High urinary sodium-to-potassium ratio is considered a strong risk factor for hypertension. This study aimed to evaluate urinary excretion of sodium and potassium, and we analyzed these levels associated with dietary intake in Japanese adolescent football players. This cross-sectional study included 120 Japanese male adolescent football players. Over 24 h, urine was collected and measured for creatinine, sodium, and potassium levels. A dietary assessment was performed using a self-administered diet history questionnaire. The study analyzed 79 participants. The mean urinary sodium was 143.2 mmol/day, urinary potassium was 42.8 mmol/day, and the mean urinary sodium-to-potassium ratio was 3.6. Compared with the Japanese Dietary Reference Intakes, the estimated salt intake was 73.4% for the participants who exceeded the sodium intake, and the estimated potassium intake was 73.4% for the participants who did not satisfy it. Multiple regression analysis revealed that milk and dairy product intake was independently and positively associated with urinary potassium (β = 0.252) and independently and negatively associated with the urinary sodium-to-potassium ratio (β = −0.254). Adolescent football players had a high-sodium and low-potassium diet, well above the Japanese Dietary Reference Intakes recommendations. Milk and dairy products could be effective for increasing urinary potassium and decreasing the urinary sodium-to-potassium ratio.